PLASMA NUTFAH HIJAUAN PAKAN TERNAK SEBAGAI SUMBER BIBIT DAN VISITOR PLOT - Hutasoit, Rijanto; Sirait, Juniar; Tarigan, Andi (Pastura; Vol 5 No 1 (2015): Pastura Vol. 5 No. 1 Tahun 2015DO - 10.24843/Pastura.2015.v05.i01.p10, 2017)
Lack of information to get the seeds and knowledge in cultivation is one of the obstacles in the implementation of the development of forage. One source of seeds that can assist in the Goat Research Station, Sei Putih North Sumatra. Various types of fodder crops maintained was an forage Germplasm, there are 85 species of forage consisting of 40 grass species and 45 types of Legume. The activity was held in 1997 and designated as visitor plots in 2000 with an average of 80 visitors per year consisting of Farmers, Extension and Students. Germplasm useful as sources of seed, for users who want to plant forage can get it according to the type and desired criteria. Currently there are 90 Ha of land that is developed from the Germplasm, some of forage have been Introductions with criteria of high production, easy to grow, palatable and drought resistant as: Paspalum atratum, Paspalum gueonarum, Braciaria ruziziensis, Brachiaria humidicola, Brachiaria brizantha, Stenotaphrum secondatum, Kinggrass, Stylosanthes guianensis CIAT 184, Arachis pintoi, Arachis glabrata, murberry and Indigofera. Keywords: Germplasm, Visitor plot, Introductions.